Bifunctional CoNx embedded graphene electrocatalysts for OER and ORR: A theoretical evaluation. (April 2018) - Zhang, Xilin; Yang, Zongxian; Lu, Zhansheng; Wang, Weichao
Abstract: The bifunctional catalysts for both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are of importance to the development of electrochemical energy systems such as reversible fuel cells, metal-air batteries, and water electrolyzers. Here, using the first-principles methods based on density functional theory (DFT), the Co and N codoped graphene systems (CoNx -gra, x = 1–4) with high ORR activity were further suggested as efficient OER catalysts. It was found that the activity on Co site of CoNx -gra towards ORR and OER would be affected by both the N-dopant concentration and configuration. The extrapolated overpotential of 0.37 V for either ORR or OER on CoNx -gra systems is comparable to those of noble metal benchmark catalysts. The origin of the activity stems from moderate hybridization between Co 3d orbital and p-orbital from O species, governed by the neighboring N coordination environment. Our results highlight the potential application of transition metal and non-metal codoped graphene as efficient non-precious bifunctional catalysts. Graphical abstract: Image 1